Structure and chain polarization of long polyynes investigated with infrared and Raman spectroscopy - Agarwal, N. R.; Lucotti, Andrea; Fazzi, Daniele; Tommasini, Matteo; Castiglioni, Chiara; Chalifoux, W. A.; Tykwinski, Rik (Journal of Raman Spectroscopy, 2013)
Symmetrically and unsymmetrically endcapped polyynes (triisopropylsilyl - TIPS - and super trityl endcapping groups) have been studied with density functional theory calculations and Raman and infrared spectroscopy. This spectroscopic investigation provides general guidelines for studying the vibrational and structural features of sp-carbon-based materials, which nowadays are at the center of growing interest for the potential applications of nanostructured carbon materials in molecular electronics. On the basis of the description of Cï£¿C stretching modes of polyynes in terms of longitudinal optical phonons of the parent infinite sp-carbon chain, we have carried out the complete assignment of the observed infrared and Raman features in the 2300-1900 cm range, for chain lengths in the range 4-20 triple bonds. This allows demonstration of polarization effects induced by an unsymmetric structure and deviations from chain linearity in long polyynes. Copyright © 2013 John Wiley & Sons, Ltd.